Strategi Pembimbingan Karakter Religius - Hadana, Dina; Sikumbang, Ahmad Tamrin (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2024)
Radio Al-Fatih is a radio that provides guidance and counseling to listeners on religious and educational issues. This study aims to determine the pattern of religious guidance and counselling through Radio Al-Fatih Medan to improve the religious character of listeners. The method used is descriptive with a qualitative approach. The research subject is Radio Al-Fatih Medan. Data collection techniques are observation and interview. The data was analyzed in the research process. The result of this research is that the religious character guidance strategy is carried out through program planning and evaluation patterns as well as strategy formulation and implementation patterns. Some planning of Radio Al-Fatih programs with Islamic nuances such as the tahsin Al-Qur'an program and then evaluating the programs broadcast with audits. Strategy formulation includes internal strategies in the form of intense communication between speakers and listeners and external strategies of technical instruments in the form of solutions to problems both da'wah tools, da'wah administration and da'wah funds.